2019
DOI: 10.3390/rs11060729
|View full text |Cite
|
Sign up to set email alerts
|

Co-Segmentation and Superpixel-Based Graph Cuts for Building Change Detection from Bi-Temporal Digital Surface Models and Aerial Images

Abstract: Thanks to the recent development of laser scanner hardware and the technology of dense image matching (DIM), the acquisition of three-dimensional (3D) point cloud data has become increasingly convenient. However, how to effectively combine 3D point cloud data and images to realize accurate building change detection is still a hotspot in the field of photogrammetry and remote sensing. Therefore, with the bi-temporal aerial images and point cloud data obtained by airborne laser scanner (ALS) or DIM as the data s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…Using multi-source data, the Special Issue includes papers focusing on deep learning [3][4][5], multi-angle image processing [6], multi-source image fusion in heterogeneous environments [2,3,5], and object-based image analysis [5,7,8]. These interesting techniques applied various change detection applications, while most of them simultaneously mined the change information from the spectral, spatial, and temporal domains.…”
Section: Overview Of Contributionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Using multi-source data, the Special Issue includes papers focusing on deep learning [3][4][5], multi-angle image processing [6], multi-source image fusion in heterogeneous environments [2,3,5], and object-based image analysis [5,7,8]. These interesting techniques applied various change detection applications, while most of them simultaneously mined the change information from the spectral, spatial, and temporal domains.…”
Section: Overview Of Contributionsmentioning
confidence: 99%
“…With the aid of fully convolutional neuron network, Pang et al [5] proposed a co-segmentation and superpixel-based graph cuts for building change detection. By modeling the characteristics of building in a 4-dimension feature space (i.e., horizontal, vertical, and temporal), this study can further identify the building change types (e.g., "newly built", "taller", "demolished", and "lower").…”
Section: Overview Of Contributionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Different from homogeneous CD, the pixels in heterogeneous images are in different distinct feature spaces [7], and the change map (CM) cannot be obtained by simple linear operations or some homogeneous methods, which is also the main difficulty for heterogeneous CD. Over the past several decades, much attention has been paid to homogeneous CD [8], and many excellent methods have been explored [9][10][11][12][13]. With the increase of different types of satellite sensors, however, CD based on homogeneous images is far away from the practical demands [8] especially when the homogeneous images are not available.…”
Section: Introductionmentioning
confidence: 99%
“…Different from DEM, the digital surface model (DSM) accurately models shapes of the existing targets beyond terrain, representing the most realistic expression of ground fluctuation. It has been found that collaborating height change brought by DSM and texture difference extracted from RS images can get rid of variation ambiguity caused by conventional 2D change extraction, and even profitably to observe demolition and construction process in the case of inherent architectures [177,178].…”
mentioning
confidence: 99%